Learners' anxiety and self-efficacy in learning English language as a third language - Nor Suriati Othman; Universiti Sultan Zainal Abidin . Faculty of Languages and Communication (2016)
Most language learners have experienced, and many of them have suffered from the feeling of anxiousness and stress in the English Language classroom even though they are at the tertiary level of education. The existence of anxiety either high or low will impact the students' language learning. Thus, this study was designed to investigate the level of language anxiety in terms of a few classifiable variables viz gender, language proficiency and self-efficacy. 230 undergraduate students of various programmes under the Faculty of Contemporary Islamic Studies (FKI), University Sultan Zainal Abidin, Kuala Terengganu participated in this study. The respondents of the study registered for the course English for Communication J (UBI 3012). English Language was their third language of acquisition. The status of the English Language for students under this faculty is a third language after Arabic Language which is considered a second language. The research design of this study was a quantitative and the instrument used in this study was a set of questionnaire which was adapted from the Foreign Language Classroom Anxiety Scale (FLCAS) and the General SelfEfficacy Scale (GSES). The FLCAS consists of 32 items to assess the degree to which a respondent feels anxious in the English Language classroom, while the GSES consists of 10 items to identify the level of self-efficacy towards anxiety in learning the English Language. The data from the questionnaire was analyzed using Statistical Package for Social Science (SPSS) version 17. Two types of statistical analysis, namely descriptive statistics and inf r ntial statistics such as Kruskal-Wallis, Ind p ndent T - Test and! Pearson C efficient Correlation were applied. Based on the re ults, it was discovered that fear of negative evaluation wa the dominant factor of language anxie am ng I arner . The r ult al 0 discovered that learners experienced anxiety at a moderate level while learners' language proficiency was at a low level. The inferential statistical analysis showed that two null hypothesis were rejected and one hypothesis was accepted. Finding from the Kruskal Wallis indicated that there was a significant level between language anxiety based on language proficiency while the Independent T -Test revealed that there was no significant level between language anxiety based on gender. The Pearson Coefficient Correlation discovered that there was a negative correlation between language anxiety and self-efficacy. The outcomes from the study have revealed pedagogical implication which can be implemented in language teaching and learning.
Thesis (Degree of Master of English Language Studies) - Universiti Sultan Zainal Abidin, 2016
Includes bibliographical references (pages 181-198)
Keywords: Universiti Sultan Zainal Abidin -- Dissertations; Universiti Sultan Zainal Abidin -- Faculty of Languages and Communication -- Dissertations; Educational psychology -- Malaysia; English -- Malaysia; Self-efficacy -- Malaysia; Dissertations, Academic